Scalability Measurement of Business Process Model Using Business Processes Similarity and Complexity - Muhammad Ainul Yaqin; Riyanarto Sarno; Abd. Charis Fauzan (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
The scalability of business process model shows the ability of a system to handle the amount of provided   business   process   activity.   In   business process management, scalability is used to compare the size of a business process model to other business process models. This research focused on measuring the scalability of business process models. Every business  processes  were  modeled  using  Petri  Net. Petri Net was used as a business process model because of its simple model notation so it can be analyzed mathematically. The scalability of business processes had been done by comparing the similarity of some business processes and their scales. The similarity measurement method proposed were based on  structural  and  behavioral  using  Jaccard coefficient, whereas the number of elements of the business process model and control flow complexity were used to measure its scale. Then, the scale value (0..1) and the similarity of the business process model was calculated by the specified formula. The result is a scalability value where the greater the value of the scalability, then the growth potential of the business process is also greater.